Transportation Statistics and Microsimulation - Spiegelman, Clifford; Park, Eun Sug; Rilett, Laurence R. (Chapman and Hall/CRC, 2016)
By discussing statistical concepts in the context of transportation planning and operations, Transportation Statistics and Microsimulation provides the necessary background for making informed transportation-related decisions. It explains the why behind standard methods and uses real-world transportation examples and problems to illustrate key conc.